2002
DOI: 10.1080/03079450120106651
|View full text |Cite
|
Sign up to set email alerts
|

Coronaviruses from pheasants ( Phasianus colchicus ) are genetically closely related to coronaviruses of domestic fowl (infectious bronchitis virus) and turkeys

Abstract: Reverse-transcriptase polymerase chain reactions (RT-PCRs) were used to examine RNA extracted from mouth/nasal swabs from pheasants exhibiting signs of respiratory disease. The oligonucleotides used were based on sequences of infectious bronchitis virus (IBV), the coronavirus of domestic fowl. A RT-PCR for the highly conserved region II of the 3' untranslated region of the IBV genome detected a coronavirus in swabs from 18/21 estates. Sequence identity with the corresponding region of IBVs and coronaviruses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
163
0
15

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(185 citation statements)
references
References 45 publications
7
163
0
15
Order By: Relevance
“…The gene order of IBV is 59-replicase-S-3-M-5-N-39 UTR. We have established in this study that both pf/CH/LKQ3/03 and tl/CH/LDT3/03 have the same S-3-M-5-N gene order (the replicase and 39 UTR sequences were not determined in this study), as is the case for coronaviruses from turkeys (Breslin et al, 1999a, b;Cavanagh et al, 2001) and pheasant (Cavanagh et al, 2002). Consequently, the coronaviruses from domestic peafowl and teal are related closely to avian coronaviruses that are in group 3, and are distinct from mammalian coronaviruses that are in groups 1 and 2 (Lai & Cavanagh, 1997 tl/CH/LDT3/03, in contrast to pf/CH/LKQ3/03, was more similar to field IBV isolates from China than to the vaccine strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene order of IBV is 59-replicase-S-3-M-5-N-39 UTR. We have established in this study that both pf/CH/LKQ3/03 and tl/CH/LDT3/03 have the same S-3-M-5-N gene order (the replicase and 39 UTR sequences were not determined in this study), as is the case for coronaviruses from turkeys (Breslin et al, 1999a, b;Cavanagh et al, 2001) and pheasant (Cavanagh et al, 2002). Consequently, the coronaviruses from domestic peafowl and teal are related closely to avian coronaviruses that are in group 3, and are distinct from mammalian coronaviruses that are in groups 1 and 2 (Lai & Cavanagh, 1997 tl/CH/LDT3/03, in contrast to pf/CH/LKQ3/03, was more similar to field IBV isolates from China than to the vaccine strains.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of these clones revealed that both newly isolated avian coronaviruses had the S-3-M-5-N gene order that is typical of group 3 coronaviruses from chicken (IBV) (Boursnell et al, 1987), turkey (Breslin et al, 1999a;Cavanagh et al, 2001;Lin et al, 2002) and pheasant (Cavanagh et al, 2002).…”
Section: Partial Genome Organization Of the Two Coronavirus Strainsmentioning
confidence: 99%
“…For the amplification reaction, two primers, XCE1'/ (ACTGGTAATTTTTCAGATGG) and UTR11 Á/ (GCTCTAACTCTATACTAGCCTA) (Cavanagh et al , 2002), binding within the S1 gene and the 3?-untranslated region (UTR) of the genome, respectively, were initially used to amplify a fragment of approximately 6.5 kb of the IBV genome. However these primers were unable to amplify 6.5 kb fragments from a number of IBV strains, including N1/ 88 and N1/03.…”
Section: Methodsmentioning
confidence: 99%
“…This is also the case for a recently analyzed coronavirus from turkeys in Britain , the first demonstration of a coronavirus in turkeys beyond North America. Furthermore, viruses associated with respiratory and kidney disease in pheasants have been discovered to be very similar to IBVs (Cavanagh et al, 2002). The use of general oligonucleotides, based on the many IBV sequences available, in RT-PCRs has played an important part in the characterization of these coronaviruses.…”
Section: Avian Coronaviruses -Not Only Infectious Bronchitis Virusmentioning
confidence: 99%
“…the 'XCE' oligonucleotides in epidemiological studies of broilers in the UK, Italy and Poland (Capua et al, 1999;Cavanagh et al, 1999), and for characterization of coronaviruses in pheasants (Cavanagh et al, 2002). Although the use of the general primers with pheasant viruses illustrates their wide applicability, they are not universal; some types of IBV differ too much, e.g.…”
Section: Infectious Bronchitis Virusmentioning
confidence: 99%